Size-Dependent Differences in Biodistribution of Titanium Dioxide Nanoparticles After Sub-Acute Intragastric Administrations to Rats - D. Hendrickson, Olga; M. Pridvorova, Svetlana; V. Zherdev, Anatoly; G. Klochkov, Sergey; V. Novikova, Oksana; F. Shevtsova, Elena; O. Bachurin, Sergey; B. Dzantiev, Boris (Current Nanoscience, 2016)
Background: The human and environmental exposure to titanium dioxide is currently large-scale. Taking into account that for TiO2 the peroral route of exposure seems to be a very important route of exposure for humans, knowledge of its biodistribution and toxicity after the peroral uptake, is highly relevant for the human health risk assessment of TiO2 NPs. The present study compares the biodistribution of titanium dioxide nanoparticles of different sizes (5-10 nm and 20-25 nm) after peroral administration to rats. Methods: For comparison of the biodistributions of titanium dioxide nanoparticles, male rats were intragastrically administered with two specimens of TiO2 nanoparticles for a 28-day period at a daily dose of 250 mg/kg of body weight. Titanium dioxide was detected in rats` organs and tissues by atomic absorption spectroscopy. Results: The absorption from the gastrointestinal tract (GIT) and translocation into secondary organs of titanium dioxide occurred in a size-dependent manner. After administration of the smaller nanoparticles, titanium was found in the brain, lungs, heart, liver, kidneys, spleen, small intestine, testicles, and blood (0.004–0.227 μg/g of organ), whereas after administration of the larger nanoparticles, titanium was accumulated only in the liver, kidneys, spleen, and small intestine (0.01– 0.29 μg/g of organ). The amounts of the detected titanium are much smaller than the administered doses. After repeateddose exposures, no animal deaths or toxicity indications were observed. Conclusions: The penetration of titanium dioxide nanoparticles from the GIT of rats into the bloodstream and their translocation into secondary organs are size-dependent and has no evident toxic effect.
Keywords: titanium dioxide nanoparticles